Comparison of Clinical Presentations and Outcomes Between Patients With TGFBR2 and FBN1 Mutations in Marfan Syndrome and Related Disorders - Attias, David; Stheneur, Chantal; Roy, Carine; Collod-Béroud, Gwenaëlle; Detaint, Delphine; Faivre, Laurence; Delrue, Marie-Ange; Cohen, Laurence; Francannet, Christine; Béroud, Christophe; Claustres, Mireille; Iserin, Franck; et al. (Circulation (New York, N.Y.), 2009)
Background— TGFBR2 mutations were recognized recently among patients with a Marfan-like phenotype. The associated clinical and prognostic spectra remain unclear. Methods and Results— Clinical features and outcomes of 71 patients with a TGFBR2 mutation (TGFBR2 group) were compared with 50 age- and sex-matched unaffected family members (control subjects) and 243 patients harboring FBN1 mutations (FBN1 group). Aortic dilatation was present in a similar proportion of patients in both the TGFBR2 and FBN1 groups (78% versus 79%, respectively) but was highly variable. The incidence and average age for thoracic aortic surgery (31% versus 27% and 35±16 versus 39±13 years, respectively) and aortic dissection (14% versus 10% and 38±12 versus 39±9 years) were also similar in the 2 groups. Mitral valve involvement (myxomatous, prolapse, mitral regurgitation) was less frequent in the TGFBR2 than in the FBN1 group (all P <0.05). Aortic dilatation, dissection, or sudden death was the index event leading to genetic diagnosis in 65% of families with TGFBR2 mutations, versus 32% with FBN1 mutations ( P =0.002). The rate of death was greater in TGFBR2 families before diagnosis but similar once the disease had been recognized. Most pregnancies were uneventful (without death or aortic dissection) in both TGFBR2 and FBN1 families (38 of 39 versus 213 of 217; P =1). Seven patients (10%) with a TGFBR2 mutation fulfilled international criteria for Marfan syndrome, 3 of whom presented with features specific for Loeys-Dietz syndrome. Conclusions— Clinical outcomes appear similar between treated patients with TGFBR2 mutations and individuals with FBN1 mutations. Prognosis depends on clinical disease expression and treatment rather than simply the presence of a TGFBR2 gene mutation.